EFEKTIVITAS MODEL KONSELING BEHAVIORAL PAVLOV DENGAN TEKNIK CLASSICAL CONDITIONING UNTUK MENINGKATKAN SELF ACHIEVEMENT - Azhar, Dimas; Suranata, Kadek; Dharsana, I Ketut (Jurnal Ilmiah Bimbingan Konseling Undiksha, 2019)
This study aims to know: Effectiveness of behavioral counseling i. f. Pavlov with classical conditioning techniques through lesson study to improve self achievement. This research includes "quasi experiment". The experimental design used was Pretest Postest Control Group Design. The population of this study was the eleventh grade students of the Singaraja Undiksha Lab High School, totaling 105 people. Self-achievement data collection in this study using the self achievement questionnaire. Based on the t-test, the results of Fhit are 1.43 with a significance level of 5% with df1 = 2-1 = 1, df2 = 23-1 = 22 with Ftable 4.30, then Fhit <Ftable or 1.43 <4 is obtained. , 30. The value of ES = 0.09, ES is in the high category. The results of this study indicate that there is effectiveness in behavioral counseling i. f. Pavlov with a classical conditioning technique on the self-achievement of class XI students at Singaraja Undiksha Laboratory.Keywords: Behavioral counseling, Pavlov, self achievement, classical conditioning technique